The Effect of Work Culture on Teacher Productivity in Public Elementary Schools in the Ungaran Timur District, Semarang Regency - Bayu Kurniawan; Rosalina Br. Ginting; Qristin Violinda (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of work culture on the work productivity of teachers in SD Negeri Ungaran Timur District, Semarang Regency. This study uses a quantitative approach with the type of causal correlational research. The population in this study is all teachers of State Elementary Schools in East Ungaran District totaling 181 people, with a sample of 125 teachers selected using the Slovin formula with proportional random sampling technique. Data were collected through a closed questionnaire and analyzed using a simple linear regression test with the help of the SPSS 21 program. The results of the study showed that work culture had a positive and significant effect on teachers' work productivity with an F-count value of 537.313 > F-table 3.92 and a significance value of 0.000 < 0.05. The determination coefficient (R²) of 0.814 shows that work culture contributes 81.4% to teachers' work productivity. The resulting regression equation is Y = 30.954 + 0.805X₃, which means that every increase in one unit of work culture will increase the teacher's work productivity by 0.805. The implications of this study show the need to strengthen a positive work culture in schools through the habituation of discipline, openness, mutual respect, and commitment to increase teacher productivity in a sustainable manner.